Association between Hyperreflective Foci on Spectral-Domain Optical Coherence Tomography and Early Recurrence of Diabetic Macular Edema after Intravitreal Dexamethasone Implantation. (19th November 2019) - Kim, Kyung Tae; Kim, Dong Yoon; Chae, Ju Byung
Abstract : Purpose . To investigate the associations between hyperreflective foci (HRF) on spectral-domain optical coherence tomography (SD-OCT) and early recurrence of macular edema after intravitreal dexamethasone (DEX) implantation in eyes with refractory diabetic macular edema (DME) to bevacizumab. Methods . Medical records of patients with refractory DME to bevacizumab, who underwent intravitreal DEX implantation and 12-month follow-up, were reviewed. Eyes in which central subfield thickness (CST) increased over 50 μ m at 3 months compared with the first month after intravitreal DEX implantation were categorized into the early recurrence group, and the others were categorized into the late recurrence group. Best-corrected visual acuity (BCVA), CST, and number of HRF on SD-OCT were analyzed. Results . Twenty-nine eyes of 26 patients (16 eyes in the early recurrence group and 13 eyes in the late recurrence group) were included in this study. The numbers of HRF in entire retina, inner retina, and outer retina at baseline in the early recurrence group (11.38 ± 3.07 in entire retina, 5.44 ± 1.50 in inner retina, 5.94 ± 2.74 in outer retina) were significantly greater than those in the late recurrence group (7.54 ± 3.60 in entire retina, p = 0.006 ; 4.08 ± 1.70 in inner retina, p = 0.034 ; 3.46 ± 2.30 in outer retina, p = 0.013 ). Multivariate logistic regression analysis showed that a higher number of HRF increased the risk of early recurrence after intravitreal DEX implantation (odds ratio in entire retina: 1.518, p = 0.012 ; odds ratio in inner retina: 2.058, p = 0.027 ; odds ratio in outer retina: 1.610, p = 0.029 ). Conclusions . Higher baseline numbers of HRF on SD-OCT may be a predictive indicator of early recurrence of macular edema after intravitreal DEX implantation for DME.